Morphology and gas response of nanocomposite structures based on irradiated ensembles of multi-walled carbon nanotubes and titanium oxide - V. V. Bolotov; E. V. Knyazev; I. V. Ponomareva; V. E. Roslikov (Омский научный вестник)
Nanocomposite structures are obtained on multi-walled carbon nanotubes pre-functionalized with argon ions and nonstoichiometric titanium oxide supported by magnetron deposition (MWCNT/TiOx). The morphology of the ensembles of individual MWCNT/TiOx composite nanostructures functionalized with argon ions and the gas response of these nanostructures to NO2 and H2 S are studied. Irradiation of MWCNT layers leads to an increase in their resistance by a factor of 1.5. A change in the resistance of a MWCNT/TiOx nanocomposite upon gas adsorption repeats a similar change in the resistance of an ensemble of irradiated MWCNT, which demonstrate gas-sensitive properties characteristic of a material with p-type conductivity — a decrease in resistance during exposure in an oxidizing gas and an increase in resistance in a reducing gas.